Porous Silica Particles

By adding a gel agent to the water to the oil dispersion system to form a nanoparticle silicone gel, the problem of complex and time-consuming preparation of large pore size and large pore volume silicate materials in the prior art is solved, and the effect of simplifying the preparation process and improving the material performance is achieved.

JP7671128B2Active Publication Date: 2025-05-01AKZO NOBEL CHEMICALS INTERNATIONAL BV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020092469
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-29
Filing Date
2020-05-27
Publication Date
2025-05-01
Estimated Expiration
2040-05-27

AI Technical Summary

Technical Problem

The prior art When preparing silicate materials with macropore size and macropore volume, the process is complicated and time-consuming, and the separation efficiency of macropore materials is low.

Method used

By mixing the aqueous phase containing nanoparticle silicone and the organic phase, a dispersion or emulsification system of water in oil is formed, and a gel agent is added to the organic phase to form a porous silica gel.

Benefits of technology

The preparation process is simplified, the material preparation efficiency of large pore size and pore volume is improved, and the mechanical strength and high separation efficiency of the material are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671128000017
    Figure 0007671128000017
  • Figure 0007671128000018
    Figure 0007671128000018
  • Figure 0007671128000019
    Figure 0007671128000019
Patent Text Reader

Abstract

To provide porous silica materials with large pore sizes and high pore volume, and an improved and simpler method for preparing the same.SOLUTION: There is provided a method for producing a porous silica, comprising the step of mixing together an aqueous phase comprising nanoparticulate silica and an organic phase to form a water-in-oil dispersion or emulsion, in which the organic phase comprises an organic solvent that is insoluble or partially soluble in water and optionally comprises a non-polar organic compound that is insoluble in water and at least partially soluble in the organic solvent, and a gelling agent is present in the aqueous phase such that the nanoparticulate silica gets gelatinized to form the porous silica. There is obtained a porous silica having an average pore diameter in a range of 20 to 450 Å, a pore volume in a range of 0.15 to 1.2 cm3 g-1, a surface area in a range of 100 to 600 m2 g-1, and a span of 0.80 or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to materials comprising porous silica particles and methods for producing them. Porous silica particles can be used in many applications, either as such or after surface modification, and in particular as stationary phases in chromatographic separation techniques. [Background technology]

[0002] Silica-based materials are commonly used in many applications, for example as stationary phases in chromatography, as catalysts or catalyst supports, or as ion exchange materials. Different applications have different requirements, for example in particle purity, alkali metal content, pore characteristics, and mechanical strength.

[0003] An advantage of silica is that its properties can be highly tuned, for example by changing the pore characteristics or by chemically modifying the surface, which can be of great utility in separation applications, for example, because such versatility allows it to be used for many different types of separations.

[0004] A common route to make porous silica materials suitable for separation techniques is, for example, by sol-gel chemistry, where a silica precursor, such as nanoparticulate or colloidal silica, is gelled under controlled conditions. Such a technique is described in EP 0298062. This typically produces porous silica with an average pore diameter of up to 100 Å. Such silica can be used to separate relatively small molecules, for example those with a molecular weight of 10000 Da or less. However, for the separation of larger molecules, such as proteins, which have a significantly larger molecular weight, larger pores are preferred, typically greater than 200 Å, often on the order of 300 Å.

[0005] Such large pore materials can be made by Ostwald ripening of silica precursor materials (e.g., those with pore sizes on the order of 100 Å), but this is a time-consuming process that often consumes silica that has value in its own right, for example as a separation medium for small molecules or as a catalyst support. In addition, it can be laborious and time-consuming to produce the silica starting material to arrive at the final large pore product with the required characteristics.

[0006] Other techniques for making large pore silica are described in US Pat. Nos. 3,855,172 and 4,874,518.

[0007] However, a further problem with prior art materials is that large pore size is often accompanied by a relatively large pore volume, which can negatively impact separation performance. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] European Patent No. 0298062

[0009] [Patent Document 2] U.S. Pat. No. 3,855,172 [Patent Document 3] U.S. Pat. No. 4,874,518 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention aims to provide an improved and simpler method for preparing porous silica materials, which can help produce silica with large pore sizes and large pore volumes. [Means for solving the problem]

[0011] In one aspect, the invention relates to a method of producing porous silica, in which an aqueous phase comprising nanoparticulate silica and an organic phase are mixed together to form a water-in-oil dispersion or emulsion, the organic phase comprising an organic solvent that is insoluble or partially soluble in water, and optionally also a non-polar organic compound that is insoluble in water and at least partially soluble in the organic solvent, and a gelling agent is added to the aqueous phase of the dispersion or emulsion such that the nanoparticulate silica gels to form porous silica.

[0012] In another aspect, the present invention provides a pore structure having an average pore diameter and / or median pore diameter (D50) in the range of 20 to 450 Å, an average pore diameter (D50) in the range of 0.15 to 1.2 cm 3 g -1 Pore ​​volume in the range of 100-600m 2 g -1 and a span of 0.80 or less.

[0013] In yet another aspect, the invention relates to a separation column or vessel containing porous silica.

[0014] In a further aspect, the present invention relates to the use of porous silica as a stationary phase in chromatography. [Brief description of the drawings]

[0015] [Figure 1] 1 is an exemplary plot of cumulative pore volume versus pore diameter for a porous material, highlighting how to interpret the D10, D50, and D90 values. [Diagram 2] 1 is an electron microscope photograph of silica particles according to the present invention (Example 70). The scale bar represents a length of 5 μm. [Diagram 3] 3 is an electron micrograph of silica particles according to the present invention (Example 70) at a higher magnification than that of FIG. 2. The scale bar represents a length of 500 nm. [Figure 4] 1 is a plot of pore volume versus pore diameter for silica according to the invention and for comparative silicas. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] [Porous Silica] The porous silica typically contains up to 10% by weight of other oxide components. In embodiments, up to 5% by weight of other oxide components are present. The other oxide components may be other refractory oxides, such as oxides of aluminum, titanium, iron, chromium, zinc, zirconium, magnesium, calcium, and cerium.

[0017] The alkali and alkaline earth contents are also typically low, for example less than 1 wt. % combined, and in a further embodiment less than 0.1 wt. %, for example less than 100 ppm.

[0018] In an embodiment, the silica contains no more than 0.1% by weight, such as no more than 100 ppm, of any other oxide or alkali / alkaline earth metal impurities.

[0019] Exceptions to the above levels of other oxides are embodiments in which the surface of the porous silica, or the surface of the nanoparticulate silica used to make the porous silica, has been deliberately modified or doped, as described in more detail below, in which embodiments up to 10% by weight aluminum oxide may be present, for example up to 5% by weight aluminum oxide.

[0020] In an embodiment, the porous silica has a particle size of 0.15 to 1.2 cm 3 g -1 , e.g., 0.5-1.0 cm 3 g -1 , or 0.8~1.0cm 3 g -1 The pore volume may be in the range of

[0021] In embodiments, the average pore diameter of the porous silica can be in the range of 20 Å to 450 Å, such as, for example, 80 Å to 450 Å, or 100 Å to 330 Å.

[0022] In an embodiment, the porous silica has a particle size of 100 to 600 m 2 g -1 The specific (total) surface area may be in the range of

[0023] In embodiments, the porous silica may have a median pore diameter of from 20 to 450 Å, such as from 80 to 450 Å, such as from 120 to 380 Å.

[0024] This method combines a median pore diameter and / or mean pore diameter in the range of 210-450 Å with a mean pore diameter of 0.80-1.2 cm 3 g -1 , e.g. 0.81~1.0cm 3 g -1 It is possible to produce porous silica having a pore volume in the range of

[0025] The median pore diameter may optionally be referred to as the "D50" pore diameter. Pores having a diameter equal to or less than the median (D50) pore diameter contain 50% of the total pore volume of the material. Similarly, a "D10" or "D90" pore diameter is the diameter within which 10% or 90% of the pore volume is contained, respectively. Thus, pores having a diameter equal to or less than the D10 or D90 diameter contain 10% or 90% of the total pore volume, respectively. The D10, D50, and D90 points are shown in FIG. 1.

[0026] Pore ​​size distribution is a measure of the spread of pore sizes in a material. It can be conveniently expressed by the ratio D90 / D10. A smaller number indicates a narrower spread of pore sizes. Another measure is the span, i.e., calculated by the formula [D90-D10] / D50.

[0027] In an embodiment, the span is less than or equal to 0.80, for example in the range of 0.05 to 0.80, for example in the range of 0.10 to 0.80 or 0.30 to 0.80.

[0028] The preferred method for measuring pore size distribution, as well as D10, D50 and D90 pore diameters is by the Barrett-Joyner-Halenda (BJH) method based on nitrogen adsorption / desorption, especially from desorption isotherm.The preferred method for measuring surface area, pore volume and average pore diameter (from surface area and pore volume) is by the Brunauer-Emmett-Teller (BET) method, also based on nitrogen adsorption / desorption, where surface area is typically calculated from the linear part of the isotherm.Examples of such methods are given in ISO 9277:2010 (for BET) and ISO 15901-2:2006 (for gas adsorption / desorption).

[0029] Porous silica is typically composed of micrometer-sized porous particles, i.e. typically has an average particle size (diameter) in the range of 1 to 100 μm, for example an average diameter of 2 to 50 μm or 4 to 20 μm.

[0030] This method allows for great control over the pore characteristics of the porous silica, including the ability to produce porous silica having large pore volumes and large average and / or median pore diameters with high order (i.e., a relatively narrow pore size distribution).

[0031] Porous silica with large pore volume and pore diameter is particularly effective as a stationary phase for the separation of large molecules (e.g., proteins).This is because the pore size is large enough to allow the adsorption of such large molecules while maintaining a pore volume large enough to ensure high separation efficiency, but therefore a large amount of stationary phase material will certainly be required.Also, by ensuring that the pore volume is not too large, the mechanical strength and integrity of the porous silica can be maintained, thus avoiding damage to the material, for example, during packing of a separation column, and again ensuring high separation efficiency.

[0032] Porous silica is typically prepared in a liquid phase process, as described further below.The porous silica is then typically removed from the liquid phase, usually by, for example, filtration, decantation, or centrifugation, to form a solid phase, for example, a dry powder.In an embodiment, the porous silica can then be packed into a separation column, for example, an HPLC column.

[0033] The porous silica can be provided in solid form, for example as a dry powder. In embodiments, the porous silica can be packed into a separation column, for example an HPLC column. In dry powder form, the particle size (diameter) can be in the range of 0.5-100 μm, for example 0.7-50 μm, 0.8-30 μm, or 1-25 μm. In embodiments, these can be sieved to give narrower, more specific ranges of particle size.

[0034] [Organo-modified silica] In an embodiment, the porous silica comprises one or more organic groups, such as one or more C 1~ C 30 an aliphatic group or one or more C 5~10 Aromatic group, or C 5~10 The aromatic or heteroaromatic group may be modified by a heteroaromatic group (hereinafter, an "A" group). In embodiments, the aromatic or heteroaromatic group is 5~6 It is an aromatic or heteroaromatic group.

[0035] In A, the aliphatic organic group is, for example, -OR, -C(O)O - , -C(O)OR, -C(O)NR 2 , -OC(O)R, -NRC(O)R, -NR-C(O)-NR 2 , -NR 2 , -[NR 3 ] + , halide, epoxy, oxo, C 5~6 Aromatic group, C 5~6 Heteroaromatic groups, C 5~6 Heterocyclic aliphatic groups, and groups of the general formula -[O-(CR a 2 )n ] m -OR b and optionally substituted with one or more groups selected from the glycol ether groups:

[0036] In A, the aromatic organic group is, for example, -OR, -C(O)O - , -C(O)OR, -C(O)NR 2 , -OC(O)R, -NRC(O)R, -NR-C(O)-NR 2 , -NR 2 , -[NR 3 ] + , halide, epoxy, oxo, C 1~30 aliphatic group, C 5~6 Heterocyclic aliphatic groups, and groups of the general formula -[O-(CR a 2 ) n ] m -OR b and optionally substituted with one or more groups selected from the glycol ether groups:

[0037] Each R group is independently hydrogen, C 1~30 aliphatic group, C 5~6 Aromatic group, C 5~6 Heteroaromatic groups, and C 5~6 heterocyclic aliphatic groups, each R a is hydrogen and C 1~4 alkyl group, each R b The group is hydrogen or C 1~10 It is an alkyl group, n is an integer of 2 to 3, and m is an integer of 2 to 20.

[0038] Any aliphatic or alkyl groups described herein (including those in functional groups such as alkoxy, amide, amine, and ester groups) may be linear, branched, or cyclic, and may be saturated or unsaturated. Typically, they are saturated. In embodiments, linear and branched groups are used, and in further embodiments, linear groups are used.

[0039] R groups (other than hydrogen) are hydroxyl, epoxy, C1~4 Alkoxy, carboxyl, halide (e.g., fluorine or chlorine), and -NH 2 It may be optionally substituted by one or more substituents selected from:

[0040] R a and R b Groups (other than hydrogen) are hydroxyl, C 1~4 In embodiments, R may be optionally substituted with one or more substituents selected from alkoxy, and halide (e.g., fluorine or chlorine). a The group is not halide substituted. In embodiments, R a and / or R b The group does not include any optional substituents.

[0041] Any heteroaromatic or heterocyclic aliphatic group described herein may have one or more heteroatoms in the ring selected from O, S, and N, typically O or N. In embodiments, there are no more than three heteroatoms in the ring, such as no more than two, and in further embodiments, there is only one heteroatom.

[0042] Unsaturated aliphatic groups can contain one or more double bonds and / or one or more triple bonds, in embodiments, there are no triple bonds.

[0043] Charged groups, e.g. -C(O)O - or -[NR 3 ] + For compounds containing the aryl group, these may also contain a countercation or counteranion, respectively. A cation is a group that is supported by a proton (H + ), alkali metals, alkaline earth metals, formula [NR 4 ] + where R is as defined above. The anion may be selected from ammonium or organoammonium ions of the formula: - , Cl - , Br - , and I -), hydroxides, nitrates, sulfates, chlorates, bromates, iodates, phosphates, tetrafluoroborates, hexafluorophosphates, salts of the formula R c SO 3 - and sulfonates of the formula R c RPO 3 - [wherein each R is as defined above, and each R c is C 1~30 aliphatic group, C 5~6 Aromatic groups, and C 5~6 heteroaromatic groups, which may be optionally substituted as described above for the R groups.

[0044] The modification of the silica can be achieved by reacting it with a suitable organic compound, for example an organosilane containing the required group. This can be achieved using known procedures, for example the procedures described in WO 2007 / 070001. The organosilane has the formula Si[Z] 4-y [A] y Each Z is typically a halide, hydroxyl, and lower alkoxy group, such as C 1~6 Alkoxy group, or C 1~4 In embodiments, Z is selected from a hydroxyl and a lower alkoxy group.

[0045] Each A is optionally substituted C as defined above. 1~30 aliphatic group, C 5~10 Aromatic group, or C 5~10A is a heteroaromatic group. y is an integer ranging from 1 to 3. When y is greater than 1, each A may be the same or different. When y is less than 3, each Z may be the same or different, although in embodiments, all Z groups are the same. Such compounds can be purchased commercially or prepared by known techniques, for example those described in Ullmann's Encyclopadie der Technischen Chemie in the section "Silicium-Verbindungen, Organische", and the Kirk-Othmer Encyclopedia of Chemical Technology, in the section "Silicon Compounds (Silanes)".

[0046] When an organosilane is used to modify silica, it forms one or more Si-O-Si linkages with the silica surface by reaction with one or more surface silanol groups. For convenience, this linkage is referred to as [SiO 2 ]-Si-[A] y It may be expressed by:

[0047] In other embodiments, they are of the formula HO-CR(CR 2X)A, where R and A are each as defined above, and X is a halogen, typically chlorine or bromine, preferably chlorine, can be used to modify the silica surface. These can be reacted with the silica surface using known techniques, for example those described in WO2014 / 206893. In an embodiment, each R is H or methyl. The halohydrin compounds can be purchased commercially or can be produced using known procedures, for example those described in WO2013 / 092778, Ullmann's Encyclopadie der Technischen Chemie, in the section on "Epoxidverbindungen", and also the Kirk-Othmer Encyclopedia of Chemical Technology, in the section on "Chlorohydrins".

[0048] When reacted with a silica surface (e.g., by stirring the compound with silica at elevated temperature), the hydroxyl groups react with the surface silanol groups of the silica. For convenience, this is referred to as [SiO 2 ]-O-CR(CR 2 X) It may be represented by A.

[0049] When silica is modified with two or more different organic groups, this can be achieved by using different modifying reactants (e.g., two different Si[Z] 4-y [A] y Reactants, or two different HO-C(CR 2 X) A reactants), where each reactant has a different A group. In another embodiment, Si[Z] 4-y [A] y Reactants can be used where y is at least 2 and contains two or more different A groups.

[0050] In an embodiment, the silica may be modified with one or more A groups, each of which is selected from the group consisting of C 1~30 In an embodiment, the silica is selected from the group consisting of alkyl groups, each of which is optionally substituted as described above, although in an embodiment, the alkyl groups are unsubstituted. 10~20 Alkyl groups and C 1~4 and alkyl groups, each of which is optionally substituted as described above, although in embodiments, both alkyl groups are unsubstituted.

[0051] Silica can be modified using known techniques, for example by stirring the silica with one or more organosilane compounds as defined above in an aqueous solution at basic pH. Such techniques are described, for example, in International Publication Nos. WO2007 / 070001 and WO2014 / 206893.

[0052] In other embodiments, the starting material can be organically modified to produce the silica according to the present invention, for example, organosilane compounds can be hydrolyzed to form organosilane-modified silica particles, or in other embodiments, colloidal silica starting material can be modified with organosilanes before gelation to form the silica according to the present invention, for example, using the procedures described in WO2004 / 035473 and WO2004 / 035474.

[0053] [Nanoparticulate silica] In the production of the porous silica of the present invention, a source of nanoparticulate silica is used, which may be in the form of colloidal silica, as further described below. In other embodiments, the source of nanoparticulate silica may be a solid form of silica dispersed or suspended in a liquid phase. In embodiments, the silica nanoparticles (before dispersion or suspension) are in the form of fumed silica, precipitated silica, or silica fume. In these types of silica, the primary particle size is preferably 200 nm or less, for example in the range of 4 to 200 nm. The primary particles tend to aggregate or agglomerate into larger particles and may have diameters (or effective diameters) in the range of 300 nm to 100 μm.

[0054] Crystalline forms of silica, such as quartz, may also be used, however these are preferably avoided as crystalline forms may be harmful to health.

[0055] [Colloidal Silica] In a preferred embodiment of the present invention, the source of nanoparticulate silica is colloidal silica, in which primary colloidal silica particles having diameters in the range of 2-200 nm are suspended in an aqueous medium. Typically, the level of aggregation of the primary particles is low, and the silica colloids are highly stable (i.e., do not gel or coagulate spontaneously) for periods of several months, typically 4 months or more, in embodiments 6 months or more. Colloidal silica is also often referred to as silica sol, and in this disclosure, the two terms are used interchangeably.

[0056] The degree of gelation or aggregation of colloidal silica can be described by the so-called "S value". In an embodiment, for unmodified colloidal silica, the S value is in the range of 10-95%, such as 20-90%, or 30-90%. The S value is measured and calculated as described by Iler & Dalton (Iler & Dalton; J. Phys. Chem., 60 (1956), 955-957). A high S value indicates that the silica particles are highly dispersed with a low level of aggregation. Conversely, a lower S value indicates a higher level of microaggregation.

[0057] When colloidal silicas are used, they may be aqueous sols that do not contain organic solvents or contain small amounts of organic solvents. When organic solvents are present in the aqueous colloidal silica, the concentration is, in embodiments, 10% by weight or less, for example 5% by weight or less of organic solvent. When organic solvents are present, they are preferably water-miscible, for example, C 1~6 Alkyl alcohol, C 1~6 Aldehyde, C 3~6 Ketone, C 1~6 Carboxylic acids and their C 1~6 In embodiments, when an organic solvent is present, the organic solvent is selected from one or more of C 1~6 Alcohols are selected from the group consisting of:

[0058] The aqueous colloidal silica may be basic, having a pH in the range of 8.0 to 12.0, for example 8.5 to 11.0. Other components of such sols include the presence of an alkali metal, typically one or more of lithium, sodium, and potassium, or ammonium or organoammonium ions [NR p 4 ] + [In the formula, each R p are independently hydrogen, C 1~30 aliphatic group, C 5~6 Aromatic groups, and C 5~6 heteroaromatic groups, which are selected from one or more -OH or C 1~4and optionally substituted with an alkoxy group.

[0059] Colloidal silica having a neutral or acidic pH can also be used, for example at pH values ​​from 2 to 7. In such embodiments, the silica particles may be surface modified with cations such as aluminum ions, as described, for example, in WO 01 / 98227, U.S. Pat. No. 5,368,833, and by Iler in The Chemistry of Silica, John Wiley and Sons (1979).

[0060] In an embodiment, colloidal silica is prepared from a soluble silicate (e.g., water glass) or a polysilicic acid solution. The polysilicic acid is prepared by converting the soluble silicate to a polysilicic acid (typically having a pH in the range of 1-3) by ion exchange or treatment with an acid, followed by addition of an alkali metal or [NR p 4 ] + The aqueous silica sol can be prepared by using a basic salt such as a hydroxide or silicate of the formula (I) to raise the pH to 7 or higher, typically 8 to 12, for example 8.5 to 11. Examples of suitable soluble silicates that can be used to prepare the aqueous silica sol include ammonium silicate, lithium silicate, sodium silicate, and potassium silicate, e.g., water glass.

[0061] [NR p 4 ] + or the alkali metal content is [NR p 4 or as alkali metal oxide, and is typically in the range of 0.01 to 5.0% by weight. In an embodiment, the content is 0.07 to 3.0% by weight.

[0062] The silica concentration in colloidal silica is SiO 2 and may be in the range of 1 to 60% by weight, such as 2 to 50% by weight or 3 to 35% by weight.

[0063] Colloidal silica particles are 50 to 900m 2 g -1 Within the range of, for example, 50~500m 2 g -1 Within the range of 100~450m 2 g -1 The surface area of ​​the colloidal silica particles in the silica sol can be calculated from NaOH titration according to the method of Sears (Sears; Anal. Chem., 1956, 28(12), 1981-1983).

[0064] The colloidal silica particles may have an average primary particle diameter in the range of 2 to 150 nm, such as 2 to 100 nm, or 3 to 75 nm. In a further embodiment, the particle diameter is in the range of 4 to 50 nm.

[0065] The average particle diameter can be calculated from the titration surface area using the method described in "The Chemistry of Silica", by Iler, K. Ralph, page 465, John Wiley & Sons (1979). For silica particles with a mass of 2.2 g cm -3 and based on the assumption that all particles are the same size, have smooth planar areas, and are spherical, the mean particle diameter (PD) can be calculated from Equation 1:

[0066]

number

[0067] Other methods for measuring average particle diameter include ES-DMA (electrospray differential mobility spectrometry), CLS (liquid phase centrifuge analysis), SEM (scanning electron microscopy), and TEM (transmission electron microscopy).

[0068] The density of silica sol depends, at least in part, on the silica content, but is typically between 1.01 and 1.30 gcm -3In one embodiment, the range is 1.2 gcm -3 is less than.

[0069] The viscosity of colloidal silica is typically less than 40 cP, for example less than 30 cP, particularly less than 20 cP. In an embodiment, the viscosity is less than 10 cP. These viscosities are measured at 20.0°C. The viscosity of silica sol can be measured using a conventional rotational viscometer, including the one described herein. The method that can be used is ASTM D4016-14.

[0070] In aqueous systems, colloidal silica particles are dissolved in alkali metals (e.g., K + , Na + , Li + ), and the formula [NR 4 ] + They can be dispersed in the presence of stabilizing cations which can be selected from ammonium or amino ions of the formula: where R is as defined above. Typically, these are alkali metal and ammonium (NH 4 + ) and in a preferred embodiment, ammonium ions are used. Alkali metals are preferably avoided, since their presence is undesirable for high purity chromatographic separation applications.

[0071] Examples of sols which can be used as the starting aqueous silica sol include silica sols sold by Nouryon under the names Levasil™ or Bindzil™, especially the alkali metal-free grades.

[0072] [Gelling agent] The gelling agent is a water-soluble ionic salt and is present in the aqueous phase in the methods described herein. The gelling agent may be a Bronsted acid or a salt of a Bronsted acid.

[0073] Without being bound by any theory, it is believed that the gelling agent typically assists in shielding the negative charges present on the surface of the silica nanoparticles, e.g., those present in aqueous colloidal silica, and aids in the aggregation / flocculation into larger condensed porous silica particles within the aqueous phase droplets.

[0074] Suitable inorganic anions for the acid or salt include halides (e.g., chloride, bromide, and iodide), carbonate, halates (e.g., chlorate, bromate, and iodate), perhalates (e.g., perchlorate, perbromate, and periodate), nitrate, nitrite, silicate, aluminate, sulfate, sulfite, phosphate, and phosphite.

[0075] Suitable organic ions of the acid or salt include carboxylates, e.g., one or more COOH or COO - The organic compounds of formula A include those containing the group. Typically, the organic anion contains 1 to 8 carbon atoms and 1, 2, or 3 COOH and / or COO - In embodiments, the carboxylate group can be formed in situ, for example, from hydrolysis of the corresponding acyl halide (e.g., chloride, bromide, or iodide) or anhydride. Examples of such anions include C 1~8 Examples of the carboxylate ion include a carboxylate ion, a dicarboxylate ion, a tricarboxylate ion, and the acids thereof. Specific examples of the carboxylate ion include an acetate ion, a citrate ion, and an oxalate ion, and the acids thereof.

[0076] The salt or acid may also be selected from organocarbonates, sulfonates, phosphonates, and acids thereof. Examples include those of formula R c CO 3 - , R c CO3 H, R c SO 3 - , R c SO 3 H, R c RPO 3 - , and R c RPO 3 H, wherein R and R c are as defined above and typically each contain eight or fewer carbon atoms.

[0077] When salts are used, they are typically alkali metal or alkaline earth metal salts, or salts of the formula [NR p 4 ] + In an embodiment, R p The group contains up to 8 carbon atoms.

[0078] In an embodiment, the gelling agent is an organic acid or salt. In a further embodiment, the gelling agent is selected from carboxylates, carbonates, and oxalates, and their acids. Organic compounds have the advantage that they do not leave any residues (e.g., in the form of non-volatile nitrate or phosphate moieties) on the silica surface after high-temperature calcination, a process step that may be used in preparing porous silica. For this reason, when salts are used, they are used in the form of [NR p 4 ] + A specific example of a gelling agent is ammonium acetate.

[0079] [Organic phase] The organic phase contains one or more organic solvents that are immiscible or partially soluble in water. The aqueous phase disperses in the organic phase to form a water-in-oil dispersion or emulsion. The aqueous phase droplets typically have an average droplet diameter of 100 μm or less, e.g., in the range of 0.5-100 μm, e.g., 1-70 μm, 2-40 μm, etc. Emulsions are preferred because they are small and stable enough to maintain dispersed aqueous phase droplets for extended periods of time. However, less stable dispersions can be used, e.g., when constantly stirred or otherwise agitated.

[0080] The organic solvent may have one or more polar groups that can interact with the surface of the silica nanoparticles, for example, through dipole or hydrogen bonding interactions. Thus, in embodiments, the organic solvent may be selected from those that contain one or more groups selected from esters, amides, aldehydes, ketones, alcohols (including glycols), ethers, and sulfoxides. In embodiments, the organic solvent molecules have 3 to 12 carbon atoms. The esters, ketones, and ethers, in embodiments, may be part of a cyclic structure.

[0081] In embodiments, the organic solvent is partially soluble in water under ambient conditions (i.e., atmospheric pressure and 25° C.). In embodiments, the solubility is 10% by weight or less in water (i.e., 0-100 gdm -3 ), and in an embodiment, the solubility is 0.1 to 10% by weight (i.e., 1 to 100 gdm -3 ) range. Furthermore, water is either immiscible or only partially miscible with the organic solvent. Thus, the amount of water that can be dissolved or mixed in the organic solvent is 10% by weight or less in the organic solvent, and in embodiments, is in the range of 0.1 to 10% by weight.

[0082] The organic solvent (or at least one of the organic solvents) that form the "oil" phase is liquid at standard temperature and pressure (i.e., 1.013 bara and 25°C). In embodiments, the organic solvent also has a boiling point higher than that of water, i.e., greater than 100°C, such as 110°C or higher, 150°C or higher, etc. In embodiments, the boiling point is 400°C or lower.

[0083] Examples of organic solvents that may form part of the organic phase include ethyl acetate, ethyl formate, methyl acetate, n-propyl formate, isopropyl formate, n-propyl acetate, isopropyl acetate, isobutyl acetate, n-butyl acetate, n-pentyl formate, isopentyl formate, n-pentyl acetate, isopentyl acetate, ethyl propionate, isobutyl isobutyrate, n-butyl propionate, ethyl 3-ethoxypropionate, 2-ethylhexyl acetate, acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, methyl isoamyl ketone, methyl n-amyl ketone, mesityl oxide, acetophenone, cyclohexanone, diethyl phthalate, ethyl lactate, benzyl acetate, butyrolactone, acetylacetone, methylcyclohexanone, benzaldehyde, diisobutyl ketone, diacetone alcohol, ethylene glycol, glyceryl-α-monochlorohydrin, propylene glycol, glycol ethers (e.g., propylene glycol, Examples of solvents include ethylene glycol monomethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-butyl ether, propylene glycol mono-tert-butyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether), glycol ether esters (e.g., ethylene glycol monomethyl ether acetate, ethylene glycol mono-ethyl ether acetate, ethylene glycol mono-butyl ether, ethylene glycol diacetate), n-propyl alcohol, isopropyl alcohol, n-butanol, sec-butanol, isobutanol, benzyl alcohol, phenethyl alcohol, 1-phenylethanol, diisopropyl ether, dimethoxymethane, dimethoxyethane, 1,4-dioxane, 1,3-dioxolane, tetrahydrofuran, anisole, phenetole, and dimethylformamide. Other examples of solvents include dimethyl sulfoxide, toluene, xylene, n-methyl-2-pyrrolidone, methyl chloride, chloroform, carbon tetrachloride, trichloroacetic acid, methyl bromide, methyl iodide, trichloroethylene, and tetrachloroethylene. The organic solvent may be a mixture of two or more solvents.

[0084] In embodiments, the organic solvent, or at least one of the organic solvents, is phenethyl alcohol, 1-phenylethanol, or benzyl alcohol.

[0085] [Non-polar organic compounds] In an embodiment, the organic phase comprises a non-polar organic compound. The non-polar organic compound does not contain a polar group and is typically an aliphatic or aromatic hydrocarbon, optionally substituted with one or more halogens, e.g., fluoride, chloride, bromide, or iodide, typically fluoride or chloride. In an embodiment, the non-polar organic compound is liquid at standard temperature and pressure (i.e., 1.013 bara and 25° C.). Examples include C 5~20 Paraffin, C 2~20 Haloparaffin, C 5~20 Aromatic compounds, and C 5~20 The aromatic compound or haloaromatic compound may be one or more C 1~10 Alkyl group, or C 1~10 It may contain a haloalkyl group. Paraffins and haloparaffins may be linear, branched, or cyclic, or may contain both cyclic and non-cyclic moieties.

[0086] In an embodiment, the non-polar organic compound is a non-halogenated C 6~10 It is an aromatic hydrocarbon, or a mixture of such compounds, for example selected from toluene, xylene (one or more of o-, m-, or p-xylene) and mesitylene.

[0087] A non-polar organic compound is immiscible in the aqueous phase, but is at least partially miscible in one or more other organic solvents that form the organic phase of the water-in-oil emulsion. Typically, the non-polar organic compound is completely mixed with the organic phase and does not form a separate phase. Thus, the non-polar organic compound is either fully miscible with one or more organic solvents present in the organic phase, or is used in an amount that does not exceed its solubility limit in the organic phase.

[0088] By varying the relative amounts of organic solvent and non-polar organic compound, the size of the aqueous droplets can be affected, which in turn can affect the porosity characteristics of the resulting porous silica. In addition, the non-polar organic compound can reduce the solubility of the aqueous components in the organic phase, which can reduce the shrinkage of the aqueous droplets. This helps maintain the silica particle size, as colloidal silica condenses to form particles within the aqueous emulsion droplets. Larger silica particles are advantageous because larger pores are formed when silica particles are packed together to form porous silica, increasing the available pore size and pore volume.

[0089] When the non-polar organic solvent is at least partially soluble in the organic phase, the solubility under standard conditions (i.e., atmospheric pressure, 25° C.) is, in embodiments, at least 1% by weight, e.g., at least 10% by weight, or at least 50% by weight, in one or more other organic solvents in the organic phase.

[0090] "Immiscible" in the aqueous phase means that the non-polar organic compound is completely insoluble or immiscible with water, or the solubility of water in the non-polar organic compound (and / or the solubility of the non-polar organic compound in water) is less than 0.1% by weight, e.g. less than 0.01% by weight (1 gdm -3 Less than, for example, 0.5 gdm -3 Less than or equal to 0.1 gdm -3 This means that the

[0091] [Emulsifiers, thickeners, and protective colloids] One or more emulsifiers can be used, which can be selected from organic emulsifiers, which are typically anionic, cationic, amphoteric, zwitterionic, or nonionic surfactants, and which are commonly known and commercially available.

[0092] Examples of ionic emulsifiers include fatty acids, fatty amines, and fatty acid esters and partial fatty acid esters of polyhydric alcohols (e.g., mono-, di-, or triglycerides), or their corresponding anhydrides. The fatty group is selected from the group consisting of C 6~22 It may be selected from aliphatic groups.

[0093] Further examples of emulsifiers include sorbitan esters (such as those sold under the Span™ trade name), such as sorbitan monolaurate (e.g., Span™ 20), and sorbitan monooleate (e.g., Span™ 80). Further examples include polyethoxylated sorbitan esters (such as those sold under the Tween™ trade name), such as PEG-20 sorbitan monolaurate (Tween™ 20), PEG-20 sorbitan monooleate (Tween™ 80), and polyoxyethylene sorbitan trioleate (Tween™ 85). Other examples include C 6 ~C 22 Alkyl sulfates, such as sodium dodecyl sulfate; n H 2n+1 (OC m H 2m ) p -OSO 3 - where n is 6 to 22, m is 2 to 3, and p is 2 to 4, for example, sodium lauryl ether sulfate, and C 12~14 Pareth-3 sodium sulfate;C 6~22 Alkyl glycosides, such as lauryl glucoside; n H 2n+1 C(O)N(X)CH 2 (C 4 H 4 [OH] 4 )CH 2 OH [wherein n is 6 to 22 and X is H or C 1~4 glucamides of alkyl, such as caprylmethyl glucamide, laurylmethyl glucamide, and dodecyl glucamide; 2~16Carboxylate-substituted amino acids and their salts, such as sodium or disodium cocoyl glutamate, and sodium lauroyl sarcosine; 6~22 Fatty acids and their salts, such as sodium oleate and potassium oleate; polyethylene glycol-substituted phenols having 5 to 25 glycol units, such as polyethylene glycol p-(1,1,3,3-tetramethylbutyl)-phenyl ether (available as Triton™ X-100); 6~22 Alkylamine oxides, such as lauramine oxide and C 6~22 Alkyl alcohols, such as cetyl alcohol and stearyl alcohol. Further examples include polymeric emulsifiers, such as (meth)acrylate polymers and (meth)acrylic acid polymers (e.g., polymethyl methacrylic acid), and at least one C 3~10 alkenyl group and at least one C 1~4 Examples of the polymer include organoammonium salts having alkyl groups, such as polydiallyldimethylammonium chloride (polyDADMAC).

[0094] Often in combination with an emulsifier, one or more protective colloids can be used, examples being polyvinyl alcohol, or polyvinylpyrrolidone.

[0095] The polyvinyl alcohol can be optionally saponified, partially or completely. In an embodiment, the polyvinyl alcohol has a degree of hydrolysis in the range of 70-100 mol%, for example, in the range of 80-100 mol%, or in the range of 80-98 mol%. The Hoppler viscosity in a 4% aqueous solution can be in the range of 1-70 mPas, or in other embodiments, 3-40 mPas (measured at 20°C according to DIN 53015).

[0096] One or more thickening agents may be used and are selected from, for example, water-soluble polysaccharide or protein-based thickeners, cellulose derivatives and starches.

[0097] The cellulose derivatives include alkyl cellulose ethers, hydroxyalkyl cellulose ethers, carboxyalkyl cellulose ethers, hydroxyalkyl polyoxyalkyl cellulose ethers, and mixed ethers having at least two different substituents selected from alkyl, hydroxyalkyl, carboxyalkyl, and / or hydroxyalkyl polyoxyalkyl. The alkyl groups are selected from C 1 ~C 10 It may be an alkyl group.

[0098] The cellulose ethers may have a degree of substitution (DS) ranging from 1.2 to 2.9, for example from 1.6 to 2.2, but may also reach up to 3, which means complete etherification of the cellulose. The substituents may be C alkoxy groups, e.g., methoxy, ethoxy, and / or propoxy groups. 1~4 In embodiments, the at least one thickening agent is selected from methyl cellulose, ethyl cellulose, propyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl hydroxymethyl cellulose, methyl hydroxyethyl cellulose, methyl hydroxypropyl cellulose, ethyl hydroxymethyl cellulose, ethyl hydroxyethyl cellulose, ethyl hydroxypropyl cellulose, propyl hydroxymethyl cellulose, propyl hydroxyethyl cellulose, and propyl hydroxypropyl cellulose.

[0099] Other polysaccharides that can be used include chemically modified or unmodified polysaccharides such as guar, dextran, chitin, chitosan, mannan, galactan, xylan, starch, xanthan gum, welan gum, gellan gum, alginates, arabinoxylan, glucan, and pectin.

[0100] Gelatin can also be used as a thickening agent.

[0101] [Process conditions] In the process according to the invention, nanoparticulate silica is gelled to produce porous silica.

[0102] The gelation of nanoparticulate silica is carried out in a two-phase system, comprising an organic liquid continuous phase in which is an emulsified aqueous phase.

[0103] In this method, a basic nanoparticulate dispersion (e.g., basic aqueous colloidal silica as described above) is mixed with at least one organic solvent, and optionally at least one non-polar organic compound, to form a water-in-oil dispersion.

[0104] One or more emulsifiers, thickeners, and / or protective colloids may also be present. The nanoparticulate silica is present in the emulsified aqueous phase.

[0105] The organic solvent or solvents, and optionally the non-polar organic compound, are present in the continuous organic phase.

[0106] Without wishing to be bound by theory, it is believed that the silica nanoparticles in the emulsified water phase (in the presence of a gelling agent) create a porous silica network composed of condensed silica nanospheres with water-filled voids between them. The liquid component is then removed, leaving the porous silica.

[0107] The content of silica in the total synthetic mixture (SiO 2 (based on the dry weight of the composition) may be in the range of 0.1 to 40% by weight, for example, in the range of 1 to 30% by weight, or in the range of 5 to 25% by weight.

[0108] The weight ratio of silica to gelling agent (SiO 2 The ratio of the total weight of the mixture (based on the dry weight of the mixture) may be in the range of 1:1 to 100:1, for example, in the range of 4:1 to 80:1 or 20:1 to 50:1.

[0109] The weight ratio of the organic solvent to silica (SiO 2The ratio of the dry weight of the mixture to the total weight of the component (based on the dry weight of the component) may be in the range of 2:1 to 100:1, for example in the range of 10:1 to 80:1.

[0110] When non-polar organic compounds are present, in embodiments, the weight ratio of the one or more non-polar organic compounds to the one or more organic solvents is in the range of 1:100 to 100:1, such as in the range of 1:50 to 50:1, such as 1:10 to 10:1, etc. In embodiments, the ratio is 1:5 to 2:1.

[0111] When emulsifiers, stabilizers and / or protective colloids are used, the total amount is in the range of 0.01 to 5% by weight, such as in the range of 0.05 to 2% by weight of the total synthesis mixture.

[0112] If any other ingredients are used, they may be present in the synthesis mixture in a total amount of 10% by weight or less, such as 5% by weight or less or 2% by weight or less.

[0113] In preparing the dispersion or emulsion (preferably emulsion), all components can be added simultaneously or separately. In an embodiment, the nanoparticulate silica-containing aqueous phase and the organic phase are prepared separately and then mixed together. In another embodiment, the aqueous emulsifier is first mixed with the organic phase, and then the nanoparticulate silica-containing aqueous phase (e.g., aqueous colloidal silica) is added.

[0114] The gelling agent may be present in one of the aqueous mixtures when making the dispersion or emulsion, or the gelling agent may be added once all other ingredients have been provided.

[0115] In the gelation of nanoparticulate silica, the pH of the dispersion / emulsion, or at least the pH of the aqueous phase of the dispersion / emulsion, may be in the range of 5 to 10. In order to avoid premature gelation of the nanoparticulate silica, especially when colloidal silica is used, initially, before the addition of the gelling agent, the pH is preferably basic, for example a pH of 7.5 or higher. To control the pH, an acid or base can be used, for example an organic solvent, an organic acid, or a basic compound, for example an alkali metal hydroxide, an alkaline earth metal hydroxide, ammonia or ammonium hydroxide, or [NR p 4 ] + ion [wherein R p is as defined above] (e.g., ammonium ion) can be added. In embodiments, alkali metal hydroxides and alkaline earth metal hydroxides are avoided so that no metal residues remain in the porous silica after gelation, washing, and calcination. In embodiments, an organic acid can be added to lower the pH of the aqueous phase, for example to a value below 7, for example within the range of 5-7, to induce or enhance gelation of the nanoparticulate (e.g., colloidal) silica.

[0116] An advantage of the presently described process is that it does not require evaporation of the solvent to achieve gelation, a technique commonly used in prior art processes. This makes the process less complicated and allows ambient or near ambient pressure conditions to be used (e.g., in the range of 0.8-1.2 bara). In embodiments, the synthesis can be carried out in a closed vessel, such as an autoclave, capable of synthesis at higher pressures, e.g., in the range of 0.8-10 bara, e.g., 0.8-5 bara.

[0117] The use of lower pressures may be avoided, however the process using evaporation techniques can still function, for example below 0.8 bara, such as between 0.05 bara and below 0.8 bara, for example between 0.05 bara and 0.4 bara.

[0118] The temperature of the synthesis is typically in the range of 0-100° C. However, higher temperatures (i.e., above ambient temperature) are preferably used to increase the rate of gelation. Thus, temperatures in the range of 40-100° C., or 50-95° C., can be used.

[0119] Although not required, subatmospheric pressures, such as up to 0.1 bara, can be used in the process for synthesizing porous silica. This can assist in evaporating volatile components, such as water and any low boiling solvents, or organic components, thereby reducing the volume required to subsequently separate the solid porous silica from the liquid phase portion of the reaction mixture.

[0120] To recover the large pore porous silica of the present invention, the liquid phase (i.e., the remaining liquid phase) is removed, for example, by centrifugation, decantation, or filtration. The solid silica product may then be washed and / or dried, if necessary, and optionally calcined. Calcination conditions include heating at a temperature in the range of 400°C to 900°C, for example 550 to 700°C, and at a pressure in the range of 0.5 to 5.0 bara, for example 0.9 to 2.5 bara, in air or under an oxygen-containing gas containing 5 to 100% by volume of oxygen. EXAMPLES

[0121] Three different experimental protocols were performed, the amounts of materials used are provided in Table 1 and the properties of the resulting porous silica are provided in Table 2.

[0122] Four different colloidal silicas were used in the examples. These contained ammonium ions (NH 4 + These properties were as follows: Sol 1 - 12% silica by weight, 800m 2 g -1 Sol 2 - 14% silica by weight, 400m 2 g -1 Sol 3 - 30% by weight silica, 220m 2 g -1 Sol 4 - Sol 3 diluted to 14% by weight with deionized water Sol 5 - 40% by weight silica, 130m 2 g -1 Sol 6 - Sol 5 diluted to 15% by weight with deionized water Sol 7 - Sol 5 diluted to 25% by weight with deionized water

[0123] For sols 4, 6, and 7, the deionized water contained sufficient aqueous ammonia (25%) to ensure the concentration of ammonium ions was the same as in the pre-diluted sols.

[0124] For each procedure, a 5 wt% aqueous solution of hydroxypropyl cellulose (HPC) was used as the emulsifier. It was prepared by dispersing 5 g of HPC in 95 g of deionized water at 60°C. The mixture was stirred continuously and cooled to room temperature after 1 hour. Stirring was continued for 24 hours. It was then filtered twice on a filter paper with a pore size of 5 μm and stored in a plastic container.

[0125] [Synthesis procedure 1] The oil phase was prepared by mixing phenethyl alcohol and a 5 wt % HPC solution in a round-bottom flask at room temperature and stirring for 30 minutes, at which point the mixture was completely clear.

[0126] Colloidal silica and 5M aqueous ammonium acetate (if used) were then added with constant stirring to form a water-in-oil emulsion with a white / milky appearance. After stirring for 60 minutes, the round-bottom flask was attached to a rotary evaporator in a water bath and rotated at the temperature and reduced pressure specified in Table 1.

[0127] Rotary evaporation was continued for 90 minutes, at which point nearly all of the water had been removed from the aqueous phase, resulting in a nearly entirely clear / transparent mixture. The temperature was then increased to 85°C for an additional 30 minutes, and then cooled to room temperature. The resulting porous silica was isolated by filtration on a Pyrex glass filter and dried at 90°C for 16 hours. It was then calcined in air at 650°C for 4 hours.

[0128] [Synthesis procedure 2] The oil phase was prepared by mixing phenethyl alcohol and a 5 wt % HPC solution in a round-bottom flask at room temperature and stirring for 30 minutes, at which point the mixture was completely clear.

[0129] Colloidal silica and 5M aqueous ammonium acetate were then added with constant stirring to form a water-in-oil emulsion. After stirring for 60 minutes, the round-bottom flask was attached to a rotary evaporator that was placed in a water bath maintained at the temperature specified in Table 2. The flask was rotated in the water bath at atmospheric pressure.

[0130] After heating the flask for the time and under the temperature and pressure conditions specified in Table 2, the temperature of the water bath was increased to 85° C. Stirring was continued at the same pressure for an additional 90 minutes.

[0131] The resulting porous silica was isolated by filtration on a Pyrex glass filter and dried for 16 hours at 90° C. It was then calcined in air at 650° C. for 4 hours.

[0132] [Synthesis procedure 3] The oil phase was prepared by mixing phenethyl alcohol and 5 wt% HPC solution in a round bottom flask at room temperature and stirring for 30 minutes, at which point the mixture was completely clear. Mesitylene was then added and the mixture was stirred for an additional 60 minutes.

[0133] Colloidal silica and 5M aqueous ammonium acetate were then added with constant stirring to form a water-in-oil emulsion and stirred for 60 minutes. The round-bottom flask was then attached to a rotary evaporator that was placed in a water bath maintained at the temperature specified in Table 2. The flask was rotated in the water bath at atmospheric pressure.

[0134] After the time specified in Table 2 after which gelation occurred, a post-gelation vacuum according to Table 2 was applied for a period of approximately 30 minutes. The temperature of the water bath was then increased to 85° C. and stirring was continued at the same pressure for an additional 30 minutes.

[0135] The resulting porous silica was isolated by filtration on a Pyrex glass filter and dried for 16 hours at 90° C. It was then calcined in air at 650° C. for 4 hours.

[0136] [Examples 1-71]

[0137] [Table 1-1]

[0138] [Table 1-2]

[0139] [Table 1-3]

[0140] [Table 1-4]

[0141] [Table 2-1]

[0142] [Table 2-2]

[0143] [Table 2-3]

[0144] [Table 2-4]

[0145] [Table 3-1]

[0146] [Table 3-2]

[0147] [Table 3-3]

[0148] [Table 3-4]

[0149] Table 3 is sorted to group the samples by the method of preparation, and for samples made using Synthesis Procedure 1, the samples were also grouped as either comparative or inventive depending on whether a gelling agent was used in the synthesis.

[0150] As can be seen, the method of the present invention is highly adaptable and can produce porous silica with a variety of properties, at least as diverse as conventional methods (see comparative examples above), but often with a desirable combination of large average and median pore diameters, large pore volume, and also small pore size distribution.For example, when using conventional techniques (see comparative examples), the maximum average pore diameter is 72 Å.When using the method according to the present invention, much larger pore diameters can be obtained without compromising pore volume and surface area, while still maintaining a narrow pore size distribution.

[0151] Figure 2 shows the silica particles of Example 70. The larger particles are composed of many smaller spherical particles (derived from colloidal silica starting material). This is more clearly evident in the higher magnification of Figure 3. The pores formed between the small silica spheres that make up the larger particles can also be seen in Figure 3.

[0152] [Comparative Examples 72 to 78] A relatively small pore size silica was produced by the process described in EP 0298062, similar to the procedure used above for Examples 4, 5, and 7. Silica sol 2 was used. The resulting silica had an average pore diameter of 100 Å, a pore size of 319 μm. 2 g -1 of surface area, and 0.84 cm 3 g -1 The pore volume was 100 μm.

[0153] The resulting material was then subjected to Ostwald ripening to grow the particles and increase the average pore diameter. 3 In a steel autoclave, 31 g of silica was added along with 619 g of water and 73 g of 25 wt% aqueous ammonia. The autoclave was sealed and heated to 120°C for 116 hours. After cooling to 30°C, 105 g of 63 wt% nitric acid was added. The silica was then filtered and washed with 300 g of water followed by 158 g of acetone. The silica was then dried in an oven at 90°C for 16 hours. The resulting material was Comparative Example 72.

[0154] This process was reproduced six more times (Comparative Examples 73-78). The resulting silica had the properties set out in Table 4 below.

[0155] [Table 4]

[0156] As can be clearly seen, the new inventive method is simpler than the conventional Ostwald ripening process and also achieves a significantly narrower pore size distribution (lower span value).

[0157] FIG. 4 compares the pore size distribution of an inventive example (Example 70) and a comparative example (Example 72), with the inventive example having a significantly narrower distribution.

[0158] [Examples 79-80] Example 79 involved the rehydroxylation treatment of Example 68. In this procedure, a round-bottom flask containing 2 g of the porous silica of Example 68 suspended in 60 g of deionized water was heated overnight under reflux using an oil bath. The mixture was cooled to 40° C., 1 ml of concentrated nitric acid was added, and stirred for an additional 30 minutes. The mixture was filtered using a Pyrex filter, and the solid residue was washed with copious amounts of deionized water, followed by acetone, and dried in an oven at 90° C.

[0159] Example 80 was made by taking 1.6 g of the rehydroxylated silica of Example 79, adding it to a round bottom flask with 0.94 g of pyridine and 150 ml of toluene, and heating it to boiling using an oil bath and holding at this temperature for 30 minutes, after which the volume of the liquid had decreased by about 40 ml. The oil bath temperature was reduced to 90° C., and then 1.03 ml of butyldimethylchlorosilane was added. The mixture was then heated under reflux overnight. The oil bath temperature was then reduced to 75° C., and 40 ml of ethanol was added to quench any unreacted silane, and the mixture was cooled to room temperature. The resulting solid was filtered using a Pyrex glass filter, washed with ethanol, and dried in an oven at 90° C. The solid was then calcined in air at 650° C. for 5 hours to remove the organic directing groups.

[0160] These samples are intended to be compared with commercially available silica samples (Examples 81-85 below) which are usually supplied in derivatized form (for separation purposes). In order to be able to compare the porosity characteristics of the silica, it is necessary to burn off the organic derivatizing groups.

[0161] Table 5 compares the characteristics of Example 68 with Examples 79 and 80. No significant differences were observed, so the derivatization of porous silica and the subsequent calcination treatment do not appear to have a significant effect on the inherent porous characteristics of the silica. Therefore, a reasonable comparison can be made with the commercial samples after calcination treatment to remove the organic derivatives.

[0162] [Table 5]

[0163] [Comparative Examples 81 to 85] Five different commercially available butyl-modified silicas with pore sizes of about 300 Å and particle sizes ranging from 10 to 15 μm were calcined in air at 650° C. for 5 hours to remove the organic groups. The properties are shown in Table 6.

[0164] The span of the commercial sample is significantly greater than that of the silica made by the method described herein.

[0165] [Table 6]

[0166] [Solubility experiment] To demonstrate the effect of organic solvents and non-polar organic compounds, several solubility studies were performed. All mixtures were prepared at room temperature.

[0167] [Experiment 1] Phenethyl alcohol was added to the flask. Sufficient water was added to ensure that the phenethyl alcohol was completely saturated. The water content of the organic layer was then analyzed by Karl Fischer titration. The water concentration was 7.8% by weight.

[0168] [Experiment 2] The procedure of Experiment 1 was followed, except that mesitylene was used instead of phenethyl alcohol. The water content of the organic layer was 0.03 wt %.

[0169] [Experiment 3] The procedure of Experiment 1 was followed, except that a 50 / 50 wt % mixture of mesitylene and phenethyl alcohol was used instead of pure phenethyl alcohol. The water content of the organic layer was 2.2 wt %.

[0170] These results demonstrate that the addition of non-polar organic compounds can decrease the solubility of water in organic solvents and therefore help reduce the shrinkage of emulsion droplets upon gelation. The present invention includes the following aspects. Section 1. Mean pore diameter in the range of 20-450 Å, median (D50) pore diameter in the range of 20-450 Å, 0.15-1.2 cm 3 g -1 Pore ​​volume in the range of 100-600m 2 g-1 and a span of 0.80 or less. Section 2. Next feature (i) The average pore diameter and / or the median pore diameter are in the range of 80 Å to 450 Å. (ii) the pore volume is at least 0.5 cm 3 g -1 and optionally 1.0 cm 3 g -1 Also less than (iii) the span is within the range of 0.30 to 0.80 (iv) the porous silica is modified with one or more organic groups, such as one or more organosilane groups; (v) The average particle size of the porous silica is within the range of 1 to 100 μm. Item 1. The porous silica according to item 1, wherein one or more of the following applies: Section 3. 1. A method for producing porous silica, wherein an aqueous phase containing nanoparticulate silica and an organic phase are mixed together to form a water-in-oil dispersion or emulsion, said organic phase comprising an organic solvent that is insoluble or partially soluble in water, and optionally also comprising a non-polar organic compound that is insoluble in water and at least partially soluble in said organic solvent, and a gelling agent is present in said aqueous phase such that said nanoparticulate silica gels to form porous silica. Section 4. The following conditions (i) the solubility of the organic solvent in water and / or the solubility of water in the organic solvent is less than 10% by weight; (ii) the source of nanoparticulate silica is aqueous colloidal silica (iii) the non-polar organic compound is 5~20 Paraffin, C 2~20 Haloparaffin, C 5~20 Aromatic compounds, and C 5~20 haloaromatic compounds, wherein the aromatic compound or the haloaromatic compound is selected from one or more C 1~10 Alkyl group, or C 1~10 May contain haloalkyl groups (iv) the organic solvent is selected from compounds having one or more polar groups selected from esters, amides, aldehydes, ketones, alcohols (including glycols), ethers, and sulfoxides. (v) the gelling agent is selected from organic ionic compounds and organic acids containing 1 to 8 carbon atoms; (vi) The boiling point of the organic solvent is greater than 100° C., for example, in the range of 110° C. to 400° C. Item 4. The method according to item 3, wherein one or more of the following applies: Section 5. The following conditions (i) the non-polar organic compound, or at least one of the non-polar organic compounds, is mesitylene; (ii) the organic solvent, or at least one of the organic solvents, is phenethyl alcohol Item 5. The method according to item 4, wherein one or more of the following applies: Section 6. The porous silica has the following characteristics: (i) 0.15 to 1.2 cm 3 g -1 Pore ​​volume in the range (ii) 100 to 600 m 2 g -1 Specific surface area within the range (iii) Mean pore diameter and / or median (D50) pore diameter in the range of 20 to 450 Å (iv) A span of 0.80 or less The method according to any one of paragraphs 3 to 5, comprising one or more of the following: Section 7. The following conditions (i) the gelation occurs at a pressure in the range of 0.08 to 10 bara; (ii) The gelation occurs at a temperature in the range of 40 to 100° C. (iii) the content of silica in the emulsion or dispersion is SiO 2 Based on the dry weight of the (iv) The weight ratio of silica to gelling agent is SiO2 Based on the dry weight of (v) The weight ratio of the organic solvent to the silica is SiO 2 Based on the dry weight of the (vi) The weight ratio of the organic solvent to the non-polar organic compound is within the range of 200:1 to 1:1. (vii) The porous silica is separated from the liquid phase and calcined. 7. The method according to any one of claims 3 to 6, wherein one or more of the following applies: Section 8. 8. The method according to any one of paragraphs 3 to 7, wherein the porous silica is separated from the liquid phase and, optionally after calcination, modified with one or more organic groups. Section 9. 9. The method of claim 8, wherein the porous silica particles are modified by reaction with one or more organosilane groups or one or more halohydrin groups. Section 10. 3. Use of the porous silica according to item 1 or 2 as a stationary phase in chromatography. Section 11. Item 3. A separation column or container comprising the porous silica according to item 1 or 2.

Claims

1. A method for producing porous silica having an average pore diameter in the range of 210-450 Å, a median (D50) pore diameter in the range of 210-450 Å, a pore volume in the range of 0.8-1.2 cm 3 g -1 , a surface area in the range of 100-600 m 2 g -1 , and a span of 0.80 or less, said span being (D90 pore diameter - D10 pore diameter) / D50 pore diameter, wherein an aqueous phase containing nanoparticulate silica and an organic phase mix together to form a water-in-oil dispersion or emulsion, said organic phase comprising an organic solvent that is insoluble or partially soluble in water and optionally also a non-polar organic compound that is insoluble in water and at least partially soluble in said organic solvent, and a gelling agent is present in the aqueous phase such that the nanoparticulate silica gels to form porous silica.

2. The method according to claim 1, wherein the solubility of the organic solvent in water and / or the solubility of water in the organic solvent is less than 10% by weight.

3. The method of claim 1 or 2, wherein the source of nanoparticulate silica is aqueous colloidal silica.

4. The method of claim 1, wherein the non-polar organic compound is selected from a C5-20 paraffin, a C2-20 haloparaffin, a C5-20 aromatic compound, and a C5-20 haloaromatic compound, and the aromatic compound or the haloaromatic compound may contain one or more C1-10 alkyl groups, or C1-10 haloalkyl groups.

5. The method of claim 1, wherein the organic solvent is selected from compounds having one or more polar groups selected from esters, amides, aldehydes, ketones, alcohols (including glycols), ethers, and sulfoxides.

6. The method of claim 1, wherein the gelling agent is selected from organic ionic compounds and organic acids containing 1 to 8 carbon atoms.

7. The method of claim 1, wherein the boiling point of the organic solvent is greater than 100°C.

8. The method of claim 2, wherein the non-polar organic compound, or at least one of the non-polar organic compounds, is mesitylene.

9. The method of claim 2, wherein the organic solvent, or at least one of the organic solvents, is phenethyl alcohol.

10. A method according to any one of claims 1 to 9, wherein the gelling occurs at a pressure in the range of 0.08 to 10 bara.

11. The method of claim 1, wherein the gelation occurs at a temperature in the range of 40 to 100°C.

12. The method according to claim 1, wherein the silica content in the emulsion or dispersion is in the range of 0.1 to 30% by weight, based on the dry weight of SiO 2 .

13. The method of claim 1, wherein the weight ratio of silica to gelling agent is in the range of 1:1 to 100:1, based on the dry weight of SiO 2 .

14. The method of claim 1, wherein the weight ratio of organic solvent to silica is in the range of 2:1 to 100:1, based on the dry weight of SiO 2 .

15. The method of claim 1, wherein the weight ratio of the organic solvent to the non-polar organic compound is in the range of 200:1 to 1:

1.

16. The method of claim 1, wherein the porous silica is separated from the liquid phase and calcined.

17. 17. The method according to any one of claims 1 to 16, wherein the porous silica is separated from the liquid phase and, optionally after calcination, modified with one or more organic groups.

18. 18. The method of claim 17, wherein the porous silica particles are modified by reaction with one or more organosilane groups or one or more halohydrin groups.

19. The method according to claim 1, wherein the pore volume of the porous silica is 1.0 cm 3 g −1 or less.

20. The method of claim 1, wherein the span of the porous silica is in the range of 0.30 to 0.

80.

21. The method of claim 1, wherein the porous silica is modified with one or more organic groups.

22. The method of claim 1, wherein the average particle size of the porous silica is in the range of 1 to 100 μm.

Citation Information

Patent Citations

  • Silica particles, a method for preparation of silica particles and use of the particles

    EP0298062A1

  • Silica particle, manufacture and use

    JP1989018910A

  • Uniform oxide microspheres and a process for their manufacture

    US3855172A

  • Porous silica microspheres having a silanol enriched surface

    US4874518A